Prenatal alcohol exposure alters mRNA expression for stress peptides, glucocorticoid receptor function and immune factors in acutely stressed neonatal brain - Ruffaner-Hanson, Chaselyn D.; Fernandez-Oropeza, Annette K.; Sun, Melody S.; Caldwell, Kevin K.; Allan, Andrea M.; Savage, Daniel D.; Valenzuela, C. Fernando; Noor, Shahani; Milligan, Erin D. (Frontiers in Neuroscience, 2023)
Background The amygdala, hippocampus and hypothalamus are critical stress regulatory areas that undergo functional maturation for stress responding initially established during gestational and early postnatal brain development. Fetal alcohol spectrum disorder (FASD), a consequence of prenatal alcohol exposure (PAE), results in cognitive, mood and behavioral disorders. Prenatal alcohol exposure negatively impacts components of the brain stress response system, including stress-associated brain neuropeptides and glucocorticoid receptors in the amygdala, hippocampus and hypothalamus. While PAE generates a unique brain cytokine expression pattern, little is known about the role of Toll-like receptor 4 (TLR4) and related proinflammatory signaling factors, as well as anti-inflammatory cytokines in PAE brain stress-responsive regions. We hypothesized that PAE sensitizes the early brain stress response system resulting in dysregulated neuroendocrine and neuroimmune activation. Methods A single, 4-h exposure of maternal separation stress in male and female postnatal day 10 (PND10) C57Bl/6 offspring was utilized. Offspring were from either prenatal control exposure (saccharin) or a limited access (4 h) drinking-in-the-dark model of PAE. Immediately after stress on PND10, the hippocampus, amygdala and hypothalamus were collected, and mRNA expression was analyzed for stress-associated factors (CRH and AVP), glucocorticoid receptor signaling regulators (GAS5, FKBP51 and FKBP52), astrocyte and microglial activation, and factors associated with TLR4 activation including proinflammatory interleukin-1β (IL-1β), along with additional pro- and anti-inflammatory cytokines. Select protein expression analysis of CRH, FKBP and factors associated with the TLR4 signaling cascade from male and female amygdala was conducted. Results The female amygdala revealed increased mRNA expression in stress-associated factors, glucocorticoid receptor signaling regulators and all of the factors critical in the TLR4 activation cascade, while the hypothalamus revealed blunted mRNA expression of all of these factors in PAE following stress. Conversely, far fewer mRNA changes were observed in males, notably in the hippocampus and hypothalamus, but not the amygdala. Statistically significant increases in CRH protein, and a strong trend in increased IL-1β were observed in male offspring with PAE independent of stressor exposure. Conclusion Prenatal alcohol exposure creates stress-related factors and TLR-4 neuroimmune pathway sensitization observed predominantly in females, that is unmasked in early postnatal life by a stress challenge.